Controlled Drug Delivery of Furosemides Using Floating Tablet System - Mohd. Wasiullah; Piyush Yadav; Manyata Yadav; Yadav Rahulkumar Ramchandra (International Journal of Membranes, 2025)
The development of gastroretentive drug delivery systems (GRDDS) has gained interest, particularly for drugs like furosemide with narrow absorption windows in the upper gastrointestinal (GI) tract. Furosemide, a commonly used diuretic, faces challenges due to limited bioavailability and rapid elimination, requiring frequent dosing and affecting patient compliance. This review highlights the formulation and evaluation of floating furosemide tablets as an effective strategy to enhance therapeutic efficacy. Floating tablets allow prolonged gastric retention, providing controlled release and maintaining optimal drug concentration within the absorption site. Key formulation aspects are discussed, including pre-formulation studies to assess drug-excipient compatibility, solubility, flow properties, and buoyancy, which are crucial for floating tablet stability and effectiveness. Various polymers and gas-generating agents are outlined for their roles in achieving buoyancy, improving stability, and controlling drug release. In vitro evaluation methods, such as buoyancy, swelling, and drug release studies, are examined to evaluate the tablet’s performance and release kinetics. Despite challenges like formulation complexity and variability in gastric motility, ongoing research, and optimization in GRDDS for furosemide show promising potential. Prospects in this area could lead to better management of conditions treated with furosemide and improved patient outcomes.
Keywords: Controlled release; Floating tablets; Furosemide; Gastroretentative furosemide buoyancy; bioavailability effervescent